The internal anatomy of the Perlidae - Sweet, Fayette Charles (My University, 1900)
Introduction: The insect chosen for this work is the larvae of the perla – which can be found in almost any running stream having a rocky bed. The Perlidae are insects of moderate or large size, furnished with four membranous wings; these are usually complex by reticulate. The hind pair are usually much larger and have a large anal area of more simple venation, which becomes pelicate when folded. The coxae are small, the legs, widely separated. The larvae are aquatic in their habits, and the metamorphosis slight. The family comprises a small number of insects, not especially attractive in their appearance, and having a life history of two abruptly contrasted portions. The first or nymph stage is aquatic, and the latter or adult stage, aerial. The Perlidae are classified in different orders of the Insecta by different authors; for instance in Vol. V, of the “Cambridge Natural History”, the Perlidae is classified as belonging to the order Neuroptera along with the Mallophaga, Embrudae, Sialidae, Panorpidae, Hemerobidae, Myrmelleonidae and Phryagenidae. Some other authors classify the family in the Neuroptera, but Comstock assigns it to an Order by itself, and calls that Order “Plecoptera”. The larvae of the Perla is found in clear, rocky streams, where they live on the underside of the loose stones in the running water. The larvae may be found by taking a loose rock from the stream and looking on its under side, where they will appear as small, shrimp like objects, from ¼ inch to 1 ½ inches in length, and of a dark brown color. They have a large head, somewhat wider than the thorax, and a tapering abdomen consisting of nine segments.
Citation: Sweet, Fayette Charles. The internal anatomy of the Perlidae. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Entomology; Perlidae; Neuoptera; Plecoptera; Theses